Factors influencing the type of self-acceptance in drug addicts and the relationship with subthreshold depression: evidence based on latent profile analysis - Yongqiu Li; Rufang Wang; Jun Liu; Yinghua Zhou (BMC Psychology, 2025)
Abstract Objective To study the heterogeneity and influencing factors of self-acceptance of drug addicts in compulsory isolation in 2 drug rehabilitation centers in Sichuan Province, and to analyze the effects of different types of self-acceptance on subthreshold depression in drug addicts, in order to provide useful references for improving their mental health. Methods Self-acceptance Questionnaire (SAQ), Drug use Stereotype Threat Scale(DSTS) and Center for Epidemiologic Studies Depression Scale(CES-D) were used to conduct a questionnaire survey in January 2024 on 1068 drug addicts in two compulsory isolation drug rehabilitation centers in Sichuan Province. Results Drug addicts self-acceptance can be categorized into 5 potential categories; men were more likely than women to show lower self-acceptance in the ‘low-low’(β = 0.285,OR = 0.381, p < 0.001),‘low-high’(β = 0.331,OR = 0.383,p = 0.004), and‘high-low’(β = 0.283,OR = 0.548, p = 0.033) groups compared to the ‘ high-high’ group; drug addicts with an education level of elementary school and below were categorized into the‘low -low ’ group(β = 0.642,OR = 6.173, p = 0.005);HIV-negative drug addicts were more likely to show higher self-acceptance than positive patients(β = 0.418,OR = 2.427, p = 0.034)); the‘low-low’group had the greatest likelihood of being alienated(β = 0.169,OR = 3.249, p < 0.001). The results of multiple linear regression showed that drug addicts in the‘ moderate-moderate ’group and‘high-high ’group had significantly lower subthreshold depression than those in the‘low-low ’group; the results of the Kruskal-Wallis Test showed that the‘high -high ’group had the lowest level of subthreshold depression, and the‘low -low ’,‘low-high ’and‘high-low ’groups had the highest mean ranks in different dimensions of subthreshold depression(P < 0.001). Conclusion Heterogeneity exists in drug addicts’ self-acceptance, and gender, HIV-positive or not, education level, and drug use stereotype threat are factors influencing self-acceptance in compulsory isolated drug addicts. High self-appraisal-high self-acceptance had the lowest level of subthreshold depression in drug addicts, and the consistency of poor self-appraisal and self-acceptance also affected the level of subthreshold depression in drug addicts.